Peta Pola Sebaran Daya Beli Penduduk dan Pasar Retail Kota Banjarmasin - Muttaqin, Hidayatullah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
This study aims to map the estimated purchasing power of residents across 52 sub-districts in Banjarmasin City and to analyze the visual relationship between purchasing power and the distribution of retail markets. The data used include the 2017 Per Capita Monthly Consumption Expenditure from BPS and the 2018 PODES data, with the proportion of households in slum settlements and health subsidy recipients serving as proxies, which were processed into a Composite Welfare Index. The analysis reveals a significant disparity in purchasing power, ranging from IDR 1,030,976 to IDR 1,818,254 per capita. Sub-districts in the southern part of Banjarmasin generally exhibit the lowest purchasing power, while the northern and central areas are above the city average. Traditional markets are concentrated in the city center, whereas minimarkets are evenly distributed, primarily following areas with high purchasing power. These findings underscore the importance of spatial mapping-based policies to reduce economic disparities and optimize the distribution of retail services in urban areas.